Isolation and characterization of pathogenic leptospires from rodents and small mammals captured in human leptospirosis suspected areas in Selangor, Malaysia - Azhari, Nurul Natasya (2018)
Leptospirosis, previously known to be a neglected zoonotic disease in the tropical region is now re-emerging as a threat to public health in both urban and rural settings. It is known that rodents are the major carrier of pathogenic Leptospira sp. In Malaysia, the endemicity of leptospirosis in human is concentrated in areas where rats were highly populated such as in residential and recreational areas with improper trash management and poor sanitation. The statistics in Malaysia has shown an increasing trend of suspected leptospirosis cases and reported deaths since it has been gazetted as a notifiable disease in 2010. This makes an urgent call to study the carrier status of pathogenic leptospires infecting the human through the study of Leptospira sp. in rodents and small mammals in Malaysia. The objective of this study is to identify and characterize the predominant pathogenic Leptospira sp. circulating in the leptospirosis suspected areas in the Selangor state of Malaysia. The study was carried out from January 2016 to April 2017 in six suspected areas comprising of urban, semi-urban and recreational forest areas. The study sites were identified by the Selangor State Health Department as outbreak or hotspot areas. Rodents trapping was performed in all six study sites. The trapped rodents were dissected and kidneys harvested. The rodent kidneys were subjected to Leptospira isolation by culture and dark-field microscopy. The identification and pathogenic strain of the isolated leptospires were determined by PCR approach. The characterization included secY and lipL32 PCR and multi-locus sequence typing (MLST). A total of 14 small mammals species were identified from the 266 captured small mammals with Rattus norvegicus (66%, n=100) being the dominant rat species in the urban area while Maxomys whiteheadi (30%, n=23) dominated the recreational forest area. Among the 266 rodents captured, 217 kidney samples were cultured, while for the remaining 49 samples, DNA was directly extracted from the kidney. From 217 samples cultured 55 (25.3%) were positive for spirochetes examined under the dark-field microscope (DFM). Of the 55 culture and 49 DNA samples, 38/266 (14.3%) were identified to be positive for pathogenic Leptospira confirmed by secY and lipL32 PCR. Phylogenetic analysis by secY PCR showed unique clusters for each species and all isolates clustered according to the respective species. Leptospira interrogans dominated all studied sites followed by L. kirschneri (n=5), L. borgpetersenii (n=2) and L. weilii (n=1). However, no significant association was shown between the infection rate in small mammals with three different sites category (urban, semi-urban and recreational forest) (chi-square, x2 0.5296; p= 0.767). From MLST analysis, three clones of Leptospira sp. were found to dominate the study sites; L. interrogans serovar Bataviae ST50, L. kirschneri serovar Grippotyphosa ST110 and L. borgpetersenii serovar Javanica ST143. While with the help of curator of MLST database, a new ST number (ST238, ST242 and ST243) representing new L. interrogans and L. weilii species was curated for samples isolated mostly from the recreational forest area sites. From the present study, R. norvegicus was identified as the common pathogenic Leptospira host dominating the urban area followed by R. rattus. However although M. whiteheadi dominated the recreational forest area, S. muelleri was the major carrier of the pathogenic Leptospira. In conclusion two species of rats (R. norvegicus and S. muelleri) were identified to play a vital role in environmental contamination in all study sites. This study also confirms for the first time, carriers of Leptospira locus ST110 L. kirschneri, ST242 L. weilii, ST238 L. interrogans and ST243 L. interrogans among small mammals in Malaysia. Thus further research and attention on the serovar status, of all isolates should be carried out as these species may potentially become highly pathogenic serovars contributing to increased risk of severe leptospirosis in Malaysia. In addition, these strains should be included into MAT panels as to improve the diagnosis in the future.